MANAJEMEN PENDIDIKAN AGAMA ISLAM BERBASIS ENTREPRENEURSHIP DI ERA INDUSTRI 4.0 (STUDI KASUS DI STF MUHAMMADIYAH TANGERANG) - Legi Yoga Shalsabik; Wahyu Fajar Nugraha (Tadarus Tarbawy : Jurnal Kajian Islam dan Pendidikan, 2022)
In the Era of Industrial Revolution IV.0, the need for entrepreneurship is a necessity, the internet-based information technology develops. Online sales growth that happened over time cannot be dammed by the rate of development, so it has an impact on the economic growth of the community that continues to increase. The main opportunity for the development of Information Technology (IT) is opening opportunities for small communities to utilize online sales as an entrepreneurial medium. Judging from the development of online-based sales that are now flourishing, it should be a concern for the manager of Islamic education to reconstruct the entrepreneur-based curriculum to create graduates' outputs who have competence in the field of entrepreneurship so that they can compete in the global arena in the industrial era 4.0. The research uses a case study approach by using data sourced from documentation, field observations, and interviews at the Senior High School Muhammadiyah Pharmacy in Tangerang.